Beyond essentialism Bulgarian inclusive nationalism: The case of the Turkish minority - Grouev, Ivaylo (University of Ottawa (Canada), 2005)
In the following pages I try to present my interpretation of the enigma behind the successful co-existence between the two largest ethnic groups in Bulgaria---the Bulgarian majority and the Turkish minority---by offering a new theoretical rationalization of this atypical phenomenon in the context of the Balkans. My hypothesis is that the Bulgarian national project was defined as a manifestation of a political attachment. With this element as the common denominator/anchor, which resulted in the supremacy of common citizenship over ethnic and religious loyalties, I argue that the Bulgarian national vision clearly contradicted other South-eastern European nationalisms known to emphasize a populations cultural heritage and its ethnic continuity. I argue that in the case of Bulgaria we are dealing with a political, civic, inclusive nationalism. Using L. Greenfeld's situational constraint theory I assess those critical variables/factors of the Bulgarian nation-building process, which, I argue, enabled the emergence of a political and inclusive national project. This path contrasted other Balkan states, where this process emphasized ethnicity and religion, rather than citizenship, as major criteria for establishing a persons membership in the national "imagined community." Hence the Bulgarian liberation movement was atypical in terms of the pattern of regional nation building where the subordination of citizenship rights to the principle of statehood was generally the norm. Yet, while this may be attributed in part to the absence of certain conditions (religious or ethnic fervour, for example), Bulgaria's national project seems to have been the result of a conscious adoption of political universalism.
Keywords: Political Science, General.; Sociology, Ethnic and Racial Studies.